2018
DOI: 10.3389/fmolb.2018.00107
|View full text |Cite
|
Sign up to set email alerts
|

Human D-Amino Acid Oxidase: Structure, Function, and Regulation

Abstract: D-Amino acid oxidase (DAAO) is an FAD-containing flavoenzyme that catalyzes with absolute stereoselectivity the oxidative deamination of all natural D-amino acids, the only exception being the acidic ones. This flavoenzyme plays different roles during evolution and in different tissues in humans. Its three-dimensional structure is well conserved during evolution: minute changes are responsible for the functional differences between enzymes from microorganism sources and those from humans. In recent years sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 122 publications
1
57
0
Order By: Relevance
“…In contrast, a pathway which does not require PLP for H 2 S synthesis involves two enzymes, D-amino acid oxidase (DAO) and 3-MST. Here, DAO catalyzes D-cysteine to 3-mercaptopyruvate, the substrate for 3-MST ( Figure 1 ) ( Shibuya et al., 2013 ; Pollegioni et al., 2018 ).…”
Section: H 2 S-producing Enzymes and Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a pathway which does not require PLP for H 2 S synthesis involves two enzymes, D-amino acid oxidase (DAO) and 3-MST. Here, DAO catalyzes D-cysteine to 3-mercaptopyruvate, the substrate for 3-MST ( Figure 1 ) ( Shibuya et al., 2013 ; Pollegioni et al., 2018 ).…”
Section: H 2 S-producing Enzymes and Pathwaysmentioning
confidence: 99%
“…In the cysteine catabolism pathway, CAT converts L-cysteine and α-ketoglutarate into glutamate and 3-mercaptopyruvate (3-MP), as stated above. 3-MP is also generated from D-cysteine by D-amino acid oxidase (DAO) ( Shibuya et al., 2013 ; Pollegioni et al., 2018 ). 3-MST then transfers the sulfur atom from 3-MP to a nucleophilic Cys 248 (the catalytic site in human 3-MST) to generate a 3-MST-bound persulfide and pyruvate.…”
Section: H 2 S-producing Enzymes and Pathwaysmentioning
confidence: 99%
“…The structures and functions of DAAO have received intense attention in recent years due to its versatility. [26][27][28][29][30] In 1995, Schell et al discovered that D-Ser was localized principally within glial cells. Specifically, they found that type-2 astrocytes, which were cultured from cerebral cortex, expressed particularly high levels of D-Ser.…”
Section: Natural Occurrence and Biological Functions Of D-amino Acidsmentioning
confidence: 99%
“…11C (depicted as predicted binding site A and B). The site A is reasonable because there is an entrance of a substratebinding pocket, in which inhibitors such as benzoate are known to bind 68) ; however, the site B was unexpected. The predicted pockets were then verified using the SEAL technology.…”
Section: Elucidation Of Ligand-binding Pocket Using Sealmentioning
confidence: 99%
“…ClarificationofLigand-BindingPocketsofhDAODimierA) Structure of 4-bromo-3-nitrobenzoic acid (BNBA); B) Structure of SEAL with a BNBA-derived ligand moiety; C) Labeled residues and computationally predicted BNBA-bindingpocketsofhDAOdimer(PDBID:2du868) ).…”
mentioning
confidence: 99%